(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2014)
In this paper, we present the propagation characteristics of Fluoropolymer based Photonic Crystal Fiber (PCF) exhibiting guiding properties in terahertz region. The variation of effective index of guided mode and dispersion with wavelength in hexagonal lattice Fluoropolymer PCF are investigated by using the fully-vectorial finite element method (FEM).